ÖĞRETMEN VE SINIF YÖNETİMİ - Veda ASLIM YETİŞ (Fırat University, 2019)
Classroom management is one of the essential factors for achieving the classroom learning. The teacher who wants to create a learning environment conducive to optimize the learning of its students and teach in this objective, must develop, deploy and update several practices, sometimes simultaneously. Teachers are prepared for this concept via their initial training and from the time they enter the classroom with teacher status, they are immediately faced with the behavior management of its learners, its courses, they are required to plan, organize and conduct their lessons in the best conditions. For this, they have to adopt professional behavior. In this study our aim was to review these behaviors, to share the teacher's attitudes ensuring an effective management of the classroom.